2022
DOI: 10.3389/fpubh.2022.986424
|View full text |Cite
|
Sign up to set email alerts
|

Associations of α-linolenic acid dietary intake with very short sleep duration in adults

Abstract: ObjectivesThis study aimed to investigate the association of α-linolenic acid (ALA; 18:3 ω-3) dietary intake with very short sleep duration (<5 h) in adults based on the CDC's National Health and Nutrition Examination Survey data.MethodsMultinomial logistic regression was used to explore the association of ALA intake with very short sleep. To make the estimation more robust, bootstrap methods of 1,000 replications were performed. Rolling window method was used to investigate the trend of the odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Acetylcholine chloride and linolenic acid are closely related to sleep 34,35 . Four metabolites are primarily involved in the regulation of actin cytoskeleton, neuroactive ligand-receptor interaction, glycerophospholipid metabolism, alpha-linolenic acid metabolism, and biosynthesis of unsaturated fatty acids pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine chloride and linolenic acid are closely related to sleep 34,35 . Four metabolites are primarily involved in the regulation of actin cytoskeleton, neuroactive ligand-receptor interaction, glycerophospholipid metabolism, alpha-linolenic acid metabolism, and biosynthesis of unsaturated fatty acids pathways.…”
Section: Discussionmentioning
confidence: 99%
“…And measurement details for all covariates are described on the NHANES website. Regarding the classification and definition of covariates, the study refers to other related studies [1,13]. Education level was categorized as below high school, high school and above high school.…”
Section: Covariatesmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD), asthma and chronic bronchitis are collectively referred to as chronic inflammatory airway diseases(CIAD) and have become an important cause of the increasing global disease burden [1,2]. According to the Global Burden of Disease 2017 data reported, smoking, household air pollution from solid fuels and ambient particulate matter were the leading risk factors for chronic respiratory disease-related disability [2].…”
Section: Introductionmentioning
confidence: 99%
“…One of them even found omega three's statistically significant negative effect on sleep disorders (Lui et al, 2021). The remaining studies showed an overall positive association between omega-3 and sleep behavior (Jansen et al, 2020;Murphy et al, 2021;Christian et al, 2016;Jackson et al, 2020;Liu et al, 2022).…”
Section: Study Selectionmentioning
confidence: 99%
“…The studies by (Christian et al, 2016), (Luo et al, 2021), (Murphy et al, 2021), (Sugimori et al, 2022), and (Zhang et al, 2022) were assessed as some concerns of bias in the third domain due to inappropriate selection of participants into research. The studies by (Luo et al, 2021), (Cheruku et al, 2022), (Liu et al, 2022), and (Zhang et al, 2022) assessed some concerns of bias and (Murphy et al, 2021) as a high-risk in the sixth domain due to discrimination arising from the outcome measurement. Figures 2 and 3 summarize the risk of bias assessment.…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%